(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Validation is recognized as a fundamental clinical component for building the therapeutic alliance and facilitating change in psychotherapy. Despite its importance, formal instruction on validation is often overlooked in training programs. This article proposes an operational definition of validation and presents a didactic systematization based on the taxonomy developed in Dialectical Behavior Therapy (DBT). It explores the conceptual foundations, clinical effects, and practical applications of validation. The six levels of validation are described, along with clinical examples for each and strategies to avoid common errors. In addition, the article offers structured training guidelines, progressive exercises, and checklists for clinical evaluation and self-assessment. The aim is to establish validation as a trainable, observable, and assessable skill within clinical contexts, supporting the development of therapists who are more competent in delivering responsive and empirically grounded interventions.